Woodstock Diary 1969 Episode 1-3 - Hegedus, Chris; Laufer, Erez; Pennebaker, D.A; Wadleigh, Michael; Myers, David; Pearce, Richard; Cocker, Joe; Hendrix, Jimi; Joplin, Janis (Warner, 2009)
August 15th 1969 was a day that went down in popular music culture when nearly 500,000 people descended on the infamous site of Woodstock to listen to 26 now-legendary artists over a 3 day period. "Woodstock Diary", featuring electrifying live footage performances of many of the bands and performers who appeared, is an enthralling ''fly on the wall'' rockumentary about the creation of Woodstock, on its fortieth anniversary and of the actual three day event itself. It contains drama, humour and even pathos and recaptures those heady days of the hippie movement when young people really believed that they could change the world. And yet incredibly this historic event almost never happened. A series of near-catastrophes conspired to derail the Woodstock Festival and but for the sheer perseverance and chutzpah of several key characters, the whole course of rock music could have been drastically different ... Directed and filmed by D.A. Pennebaker, and produced by Alan Douglas (who actually shot Woodstock), this is a 180 minute blast from the past a must have DVD title! Released to coincide with the fortieth anniversary of this momentous event. [www.amazon.co.uk]
Keywords: DVD-Video